2019
DOI: 10.1111/nph.15661
|View full text |Cite
|
Sign up to set email alerts
|

Changes in grain protein and amino acids composition of wheat and rice under short‐term increased [CO2] and temperature of canopy air in a paddy from East China

Abstract: Summary Projected global climate change is a potential threat for food security. Both rising atmospheric CO2 concentrations ([CO2]) and temperatures have significant impacts on crop productivity, but the combined effects on grain quality are not well understood. We conducted an open‐air field experiment to determine the impacts of elevated [CO2] (E‐[CO2], up to 500 μmol mol−1) and warming (+2°C) on grain yield, protein and amino acid (AAs, acid digests) in a rice–winter wheat rotation system for 2 yr. E‐[CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 41 publications
5
39
4
3
Order By: Relevance
“…The highest concentration of glutamic acid was observed in the wheat variety PBW-550 and was lowest in UP-262. The results are inconsistent with those of Wang et al ( 47 ), who found glutamic acid as the most dominant amino acid in the vicinity of 30.99–31.41 g/100 g protein in a Chinese wheat variety. Jood et al ( 48 ) also found glutamic acid as the predominant amino acid, having a concentration of 31 g/100 g protein in an Indian wheat variety.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The highest concentration of glutamic acid was observed in the wheat variety PBW-550 and was lowest in UP-262. The results are inconsistent with those of Wang et al ( 47 ), who found glutamic acid as the most dominant amino acid in the vicinity of 30.99–31.41 g/100 g protein in a Chinese wheat variety. Jood et al ( 48 ) also found glutamic acid as the predominant amino acid, having a concentration of 31 g/100 g protein in an Indian wheat variety.…”
Section: Resultscontrasting
confidence: 99%
“…Among the non-essential amino acids, aspartic acid, glycine, alanine, arginine, cystine, and proline showed significant ( p ≤ 0.05) differences, whereas serine, tyrosine, and arginine varied non-significantly ( p ≥ 0.05). Anjum et al ( 15 ); Wang et al ( 47 ); Jood et al ( 48 ) and Alijosius et al ( 49 ) reported the following concentrations of amino acids (in grams per 100 g protein): aspartic acid, 3.93–6.60; serine, 3.35–5.69; glycine, 2.81–6.78; alanine, 0.30–4.02; arginine, 1.55–7.01; tyrosine, 1.39–4.82; cystine, 2.07–2.30; proline, 7.17–15.38; threonine, 2.40–4.05; histidine, 1.23–5.24; valine, 2.99–6.59; methionine, 0.75–2.70; phenylalanine, 4.21–5.47; isoleucine, 1.89–4.04; leucine, 3.78–7.62; and lysine, 2.05–3.14. Most of the values obtained agreed satisfactorily and were within the range; however, the mean concentration of alanine was somewhat higher and those of threonine, histidine, and valine were lower than those reported previously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in comparison to those studies, relatively higher levels of Ala and Gly have been reported in the local traditional va- the amino acid composition of rice. Studies have revealed that, with increasing temperatures of the environment, notable decrease in protein yield and amino acid content in rice [38] and protein content in wheat [39] have been reported. In addition, similarly as observed with this study, Oh, et al (2019) [40] has pointed out that the amino acid composition is significantly affected by the rice variety and the location of cultivation.…”
Section: Amino Acid Composition In Rice Samplesmentioning
confidence: 99%
“…Under conditions of high day time temperatures, silicon fertilization improved grain yield and the nitrogen, phosphorus, and potassium translocation to panicles. Wang et al (2018) in eastern China performed a field experiment involving elevated CO 2 concentrations and elevated air temperatures. The enhanced CO 2 content supported greater wheat (Triticum aestivum L.) and rice yields; however, protein contents declined.…”
Section: ) Influence Of High Temperature and Other Meteorological Vamentioning
confidence: 99%